2001
DOI: 10.1055/s-2001-19928
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Approach to Intraventricular Cysticercal Lesions

Abstract: Various surgical approaches to treat intraventricular cysticercosis have been practiced over the years. We now present our experience with the use of the endoscope in the removal of intraventricular cysticercal cysts in patients with intraventricular cysticercal lesions associated with hydrocephalus. From 1995 to 1998, we have excised intraventricular cysticercal cysts from 9 patients. They were located in lateral ventricle in 4, in the third ventricle in two and in the fourth ventricle in three patients. A Ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(61 citation statements)
references
References 9 publications
3
58
0
Order By: Relevance
“…Two of these two were permanent 27,28 . Anandh et al 26 described a right transfrontal approach using a rigid endoscope to enter the lateral and third ventricle and to remove fourth ventricle cysts in three patients, followed by a standard third ventriculostomy, like we performed with our case. The authors removed the cystic lesions in all patients with no mortality and a case evolving with transient hemiparesia and ocular ptosis probably to lesion of the periaqueductal region.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Two of these two were permanent 27,28 . Anandh et al 26 described a right transfrontal approach using a rigid endoscope to enter the lateral and third ventricle and to remove fourth ventricle cysts in three patients, followed by a standard third ventriculostomy, like we performed with our case. The authors removed the cystic lesions in all patients with no mortality and a case evolving with transient hemiparesia and ocular ptosis probably to lesion of the periaqueductal region.…”
Section: Discussionmentioning
confidence: 66%
“…Endoscopic approaches for intraventricular neurocysticercosis has been described recently 7,[23][24][25][26] . Proaño et al performed an endoscopic exploration of fourth ventricle that showed a ventricle inflamatory entrapment secondary to ependymitis 8 .…”
Section: Discussionmentioning
confidence: 99%
“…[114] Most studies have been addressed to review the therapeutic approaches of IVNCC, as can be seen in our review. [99,110,[115][116][117][118][119][120][121][122][123][124][125][126][127] and has been well established that available treatment options are: medical, external cerebro-spinal fluid diversion, microsurgical, or endoscopic removal alone or in combination. [122] Summarizing the reports in the medical literature we can conclude that the best choices for treatment of IVNCC are:…”
Section: Fourth Ventricular Neurocysticercosis (Fvncc)mentioning
confidence: 99%
“…[162] Although they have also reported irreversible spinal injuries by NCCIm that logically do not recover with surgical intervention. [141] Finally, there are individual differences from the clinical point of view, imaging and of response to treatment according to the number and location of the lesions, that determine the characteristics of the presentations described [117,161] and which are by describing such as: medullary central cord syndrome, medullary conus and the horsetail, when this happens. In the meantime, report of isolated cases continues to unfold with more or less variations between the same.…”
Section: Intraspinal Nccmentioning
confidence: 99%
See 1 more Smart Citation